Who will follow the leader? Managers' perceptions of management development activities: an international comparison - Newell, H (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2004)
This article contributes to the on-going debate surrounding management education and development through an examination of the development experiences of managers studying for an MBA by distance learning at Warwick Business School. It analyses the extent to which management development opportunities, both formal and informal, are seen to support managers in their day-to-day roles and deliver those skills necessary for the future. The research also provides the opportunity to compare responses from UK managers with those from managers in other countries. The survey evidence shows that in some respects the experience of UK and Overseas respondents are quite similar; they both receive large amounts of training and development from their employers and show a preference for more ‘non-formal’ routes of learning. In other ways their experiences are quite different: UK managers take up their first full-time job and their first managerial appointment earlier than the overseas respondents and overseas respondents placed much more emphasis on networking and learning from outside their own organisations than did UK managers. The research also suggests that integrating management development activities with other human resource policies and practices, such as performance evaluation and reward remains problematic and that there is a strong perception amongst managers both in the UK and overseas that their organisations do not view management development in a strategic way. When looking at future development needs respondents from both the UK and overseas highlighted the need for leadership skills as a priority for themselves but focused on more general management and operational skills as the main priority for their colleagues. One possible explanation for this is that the respondents were only to well aware of the fact that that leaders need followers. This is, however, a view at which is at odds with current policy arguments in the UK where leadership skills are seen to be necessary for all managers.